Perancangan dan Analisa Simulasi Pembebanan Chassis Sepeda Wisata Untuk Dua Penumpang Menggunakan Software Autodesk Inventor 2017 - Salimin, Salimin; Samhuddin, Samhuddin; Adha, Ismail (Teknik Mesin Universitas Halu Oleo, 2018)
This research is aiming to know the distribution of stress, strain, displacement as well as safety factor on bike tour chassis. The chassis was designed in Autodesk Inventor software and simulated using Autodesk Inventor software. Carbon steel and load of 120 kg, 150 kg, and 180 kg was used as material for the chassis. The results of this research indicate that maximum stress at the main frame can reach around 47,86 N/m2 in simulation and 45,83 N/m2 by manual calculation. On the other hand, the maximum stress can reach 2079×10 mm/mm in simulation and 2,29×10 N/m2 in from manual calculation. The maximum displacement happened on the frame is around 0,4684 mm in simulation while in calculation it can reach around 0,528. The maximum safety factor happened on the chasis is around 7,31 in simulation while in calculation it can reach around 7,63.